KARAKTERISTIK PENYAKIT KOMORBID PADA PASIEN INFEKSI COVID-19 - Saraswati Laksmi Dewi; Ratna Kartika Dewi; Kadek Surya Atmaja (Fakultas Kedokteran, Universitas Hang Tuah, 2026)
COVID-19 is an emerging global infection with a significant impact on people's lives. This study aims to describe the characteristics of comorbidities in COVID-19-infected patients at Sanjiwani Teaching Hospital and Kasih Ibu Hospital in Denpasar. The research method used was a descriptive, cross-sectional observational study involving 115 adult patients diagnosed with COVID-19 based on RT-PCR test results. Demographic data, symptoms, laboratory results, and comorbidities were recorded. The results showed that the majority of patients were over 60 years old, with fever (78.3%) as the most common complaint. Laboratory results indicated moderate COVID-19 severity (52%) and severe-critical (47.8%). The most common comorbidities found were hypertension and diabetes mellitus. This study highlights the importance of monitoring and managing comorbidities to improve clinical outcomes for COVID-19 patients.